Antaseden Work Engagement pada Karyawan Hotel Aston di Jakarta Barat - Pasya, Rebilo; Berliyanti, Dita Oki (J-MAS (Jurnal Manajemen dan Sains), 2024)
The purpose of this study was to analyze the effect of Organizational Health and Perceived Organizational Support on Work Engagement among 4-star hotel employees in Jakarta. Data was collected from 215 employees working at 4-star hotels in Jakarta. The data collection technique used in this study was non- probability sampling with a purposive sampling method. The technique used to analyze this research is an instrumental test in the form of validity, reliability and hypothesis testing using the Multiple Regression with SPSS software. The results of testing the hypothesis in this study indicate that there is a positive influence between Organizational Health on Work Engagement and there is a positive influence between Perceived Organizational Support on Work Engagement. Managerial implications can be given to continue to increase Perceived Organizational Health and Organizational Support so that employee Work Engagement increases.